The Relationship between Self-Efficacy and Quality of Life in Hemodialysis Patients - Namira Anfi Normalitasari; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2024)
Self efficacy can strengthen adherence to treatment, which in turn increases the level of recovery and self-confidence, thus improving the quality of life of individuals. The objective of this research was to explore how self-efficacy correlates with the quality of life among individuals suffering from chronic kidney failure who are receiving haemodialysis treatment at Pandan Arang Hospital. Employing a cross-sectional methodology, the study utilised an Accidental Random Sampling method. A total of 121 participants were involved in the sample, with Self-efficacy is assessed through the utilisation of the General Self-Efficacy Scale questionnaire and quality of life assessed through the Kidney Disease Quality of Life. GSES validity and reliability results Cronbach Alpha 0.917 with 10 valid questions and KDQOL 36 validity and reliability results Cronbach Alpha 0.925 with 36 valid questions. The analytical method employed in this research involved the Spearman test to determine the relationship between self-efficacy and quality of life. The results showed respondents with self-efficacy are those with high self-efficacy, namely 90 respondents (74.4%). And the most quality of life is with moderate quality of life, namely 77 respondents (63.6%). The results of the tests revealed a significant p value of 0.001 (p < 0.05), indicating a meaningful connection between self-efficacy and quality of life. In summary, this study verifies the existence of an association.